2004
DOI: 10.1074/jbc.m404983200
|View full text |Cite
|
Sign up to set email alerts
|

NADPH Oxidase-dependent Acid Production in Airway Epithelial Cells

Abstract: The purpose of this study was to determine the role of NADPH oxidase in H ؉ secretion by airway epithelia. In whole cell patch clamp recordings primary human tracheal epithelial cells (hTE) and the human serous gland cell line Calu-3 expressed a functionally similar zincblockable plasma membrane H ؉ conductance. However, the rate of H ؉ secretion of confluent epithelial monolayers measured in Ussing chambers was 9-fold larger in hTE compared with Calu-3. In hTE H ؉ secretion was blocked by mucosal ZnCl 2 and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
164
2
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 130 publications
(174 citation statements)
references
References 54 publications
6
164
2
2
Order By: Relevance
“…2). As a result, activation of NOX leads to the activation of voltage-gated H + channels and/or other ion channels (18)(19)(20), as mechanisms of charge compensation. Original studies of NOX1 gene regulation suggested the presence of a short NOX1 splice variant with intrinsic H + channel activity (8), although this was later realized to be an artifact due to the formation of a stable loop within NOX1 mRNA (6).…”
Section: General Aspects Of Nox-dependent Signaling Production Of Celmentioning
confidence: 99%
See 2 more Smart Citations
“…2). As a result, activation of NOX leads to the activation of voltage-gated H + channels and/or other ion channels (18)(19)(20), as mechanisms of charge compensation. Original studies of NOX1 gene regulation suggested the presence of a short NOX1 splice variant with intrinsic H + channel activity (8), although this was later realized to be an artifact due to the formation of a stable loop within NOX1 mRNA (6).…”
Section: General Aspects Of Nox-dependent Signaling Production Of Celmentioning
confidence: 99%
“…The fact that ROS production by polarized epithelia occurred only apically and could be stimulated by activators of protein kinase C (82), known to activate the phagocyte NADPH oxidase (5), suggested regulated and compartmentalized epithelial ROS production by an NADPH oxidase. The source of epithelial ROS was identified only a few years ago, after initial discovery of prominent expression of the NOX homologs DUOX1 and DUOX2 within the lung (35), and studies on lung tissues using in situ hybridization and immunohistochemistry, which revealed the presence of DUOX1 at the apical surface of tracheobronchial epithelial cells, and DUOX2 within salivary and submucosal glands (19,79,83,84 (88,89), which is due to the presence of DUOX1 (90). Although DUOX expression in the lung is primarily localized to airway or alveolar epithelial cells, recent studies have also suggest the presence of DUOX proteins in lymphocytes (51,91).…”
Section: Nadph Oxidases Within the Airway Epithelium: Duox1 And Duox2mentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were whole cell patch-clamped as previously described [20]. Briefly, cells were bathed in (in mM): 120 N- [2-hydroxyethyl] Note that the solutions were Cl -free in order to exclude the contribution of Cl -currents during the measurements of the relatively small H + currents.…”
Section: Recording Of Proton Currentsmentioning
confidence: 99%
“…Measurements of intracellular pH (pH i ) were done as described [20]. Briefly, BCECF-AM (2', 7'-bis-(2-carboxyethyl)-5-(and-6)-carboxyfluorescein, acetoxy-methyl ester)-loaded cells were investigated on an inverted microscope at 400x magnification, excited at 440 nm and 495 nm and emission was collected between 525 nm and 550 nm with a cooled CCD camera (Photometrics CoolSnap HQ, Roper Scientific) controlled by a computerized imaging system (Metafluor, Universal Imaging Corp.).…”
Section: Measurement Of Intracellular Acid Productionmentioning
confidence: 99%